Demonstrations as an essential component of the democratic system - Prianto, Yuwono; Nadilatasya, Putri Meilika; Nuzan, Namira Diffany; Burnama, Yustince (Universitas Tanjungpura, 2025)
Democracy, as a system of government based on popular sovereignty, places freedom of expression as a fundamental right of every citizen. One tangible manifestation of this right is demonstrations, which serve as an essential means of channeling public aspirations toward government policies. This study aims to analyze the role of demonstrations as an essential element in strengthening Indonesia